Ethnic conflict: The role of ethnic representation - Sonia Bhalotra; Irma Clots-Figueras; Lakshmi Iyer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
We investigate the impact of the political representation of minority groups on the incidence of ethnic conflict in India. We code data on Hindu-Muslim violence and Muslim political representation in India and leverage quasi-random variation in legislator religion generated by the results of close elections. We find that the presence of Muslim legislators results in a large and significant decline in Hindu-Muslim conflict. The average result is driven by richer states and those with greater police strength. Our results suggest that the political empowerment of minority communities can contribute to curbing civil conflict.
Keywords: D72; D74; J15; 330; conflict; violence; religion; political representation; police; close elections